Reducing the risk of gastroduodenal ulcers with a fixed combination of esomeprazole and low-dose acetyl salicylic acid. (August 2011) - Yeomans, Neville D
Low-dose acetyl salicylic acid (ASA) for preventing cardiovascular and cerebrovascular events is now one of the most frequently prescribed medications in some Western countries. However, it is associated with significant morbidity and mortality as a consequence of the development of gastric and duodenal ulcers and their complications. Recent randomized controlled trials in patients who are at moderately increased risk of ulcers have shown that the proton pump inhibitor esomeprazole (the S -isomer of racemic omeprazole) reduces the gastroduodenal ulcer incidence by approximately 70––85% and the gastrointestinal bleeding risk by as much as 90%. Case––control studies also indicate that the risk of ulcer bleeding is less in low-dose ASA users who concomitantly take a proton pump inhibitor. This article reviews the pharmacology of the component agents and the evidence for efficacy of the combination of esomeprazole and low-dose ASA.